Sport nutrition for health and performance - Manore, Melinda; Meyer, Nanna L.; Thompson, Janice (United States : Human Kinetics, 2009)
This text offers the latest information available, including new research on body composition assessments, updated protein requirements for athletes, and a reexamination of various diets and techniques for weight loss.
Includes index.
Keywords: Athletes -- Nutrition; Physical fitness -- Nutritional aspects; Nutritional Physiological Phenomena; Sports Medicine -- methods; Exercise -- physiology; Food; Nutritional Requirements; Physical Fitness -- physiology